Stabilizing America's economy - Nikolaieff, George A. (New York, H. W. Wilson Co., 1972)
This compilation traces the background of our current economic difficulties, discusses the steps taken by President Nixon to revitalize the economy while halting inflation, and examines reaction to wage and price controls imposed, as well as the decision to devalue the dollar.
Bibliography: p. 245-256.
13
Keywords: Wage-price policy -- United States; America's economy; Economic policy; Economy; Devaluation of currency -- United States; United States -- Economic policy -- 1971-1981.